Analize kakovosti pridrževanja pločevine pri globokem vleku - Pepelnjak, Tomaž (Strojniški vestnik, 2001)
Due to the increasing complexity of products, forming procedures are becoming ever more demanding. As a consequence, the holding procedure is becoming better adapted to the forming process through the use of various optimisation concepts. This paper presents the modern methods for the optimisation of holding, with an emphasis on the temporary optimisation of the blankholder force and the use of elastic and segmented blankholders.
Keywords: globoki vlek; pridrževanje pločevine; optimiranje; metode končnih elementov; simuliranje; pločevina; pridržala; modeli